1967
DOI: 10.1111/j.1469-7998.1967.tb01638.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural adaptation for reducing water‐loss in three species of terrestrial snail

Abstract: Laboratory measurements indicate that observed differences in the rate of water‐loss from inactive Helix aspersa, Otala lactea and Sphincterochila boissieri are due to morphological adaptations such as a thicker shell, reduced aperture and thicker epiphragm. These modifications enable terrestrial snails to inhabit dryer environments by increasing the length of time the snail can remain inactive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
3

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 15 publications
1
32
0
3
Order By: Relevance
“…The onset of activity occurs with the beginning of the rainy season, when snails replenish their water reserves. Comparative studies in land snails have revealed that, in general, resistance to heat and aridity is correlated with distribution patterns and with abiotic environmental variation (Cameron, 1970;Machin, 1967). A series of studies on water relations and resistance to experimental desiccation of Israeli land snails have demonstrated that Mediterranean snails are less resistant than desert species and populations, and that the distribution pattern of each species and its microhabitat are related to its ability to cope with desiccating conditions (Arad, 2001;Arad, 2009;Arad et al, 1989;Arad et al, 1992;Arad et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of activity occurs with the beginning of the rainy season, when snails replenish their water reserves. Comparative studies in land snails have revealed that, in general, resistance to heat and aridity is correlated with distribution patterns and with abiotic environmental variation (Cameron, 1970;Machin, 1967). A series of studies on water relations and resistance to experimental desiccation of Israeli land snails have demonstrated that Mediterranean snails are less resistant than desert species and populations, and that the distribution pattern of each species and its microhabitat are related to its ability to cope with desiccating conditions (Arad, 2001;Arad, 2009;Arad et al, 1989;Arad et al, 1992;Arad et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The desert inhabiting S. zonata seems to have developed effective regulatory mechanisms to withstand extreme environmental conditions (Machin, 1967;Schmidt-Nielsen et al, 1972). In an interspecific study of Sphincterochila, Arad et al (Arad et al, 1989) showed that S. zonata was the most resistant species to desiccation, characterized by the lowest rates of water loss, the thickest epiphragm, the lowest epiphragm area-specific water vapor conductance and the most favorable surface-to-volume ratio, compared with all other congeners, including the Mediterraneantype S. cariosa.…”
Section: Introductionmentioning
confidence: 99%
“…The smaller mean aperture height of the shell may represent a strategy to prevent excessive water loss (GOODFRIEND 1986). MACHIN (1967), PEAKE (1978), EMBERTON (1982), andGOODFRIEND (1986), along with other investigators, have reported that smaller specimens are found in terrestrial gastropod populations living in dry areas with a strong incidence of sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…The desert-inhabiting species S. zonata developed a variety of effective morphological adaptations to withstand the severe habitat of the desert (Machin 1967;Schmidt-Nielsen et al 1972). In an interspecific study of Sphincterochila, Arad et al (1989) showed that S. zonata was the most resistant species to desiccation, characterized by the lowest rates of water loss, thickest epiphragm, lowest epiphragm area-specific water vapour conductance and the most favourable surface-to-volume ratio, compared to all other congeners, including the Mediterranean-type S. cariosa.…”
Section: Cost Benefits and Survival Strategymentioning
confidence: 99%
“…Comparative studies in land snails have revealed that, in general, resistance to heat and aridity is correlated with distribution patterns and with abiotic environmental variation (Cameron 1970;Machin 1967). A series of studies on water relations and resistance to experimental desiccation of Israeli land snails have demonstrated that Mediterranean snails are less resistant than desert species and populations and that the distribution pattern of each species and its microhabitat are related to its ability to cope with desiccating conditions (Arad et al 1992(Arad et al , 1993a(Arad et al , b, 2009).…”
Section: Introductionmentioning
confidence: 99%